2019
DOI: 10.3390/ijms20040799
|View full text |Cite
|
Sign up to set email alerts
|

Grain Legumes and Fear of Salt Stress: Focus on Mechanisms and Management Strategies

Abstract: Salinity is an ever-present major constraint and a major threat to legume crops, particularly in areas with irrigated agriculture. Legumes demonstrate high sensitivity, especially during vegetative and reproductive phases. This review gives an overview of legumes sensitivity to salt stress (SS) and mechanisms to cope with salinity stress under unfavorable conditions. It also focuses on the promising management approaches, i.e., agronomic practices, breeding approaches, and genome editing techniques to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 217 publications
(240 reference statements)
2
61
0
3
Order By: Relevance
“…The tolerance and the adaptability of a plant to stress conditions such as salinity or alkalinity are tested by the production of different organic compounds such as proline [35,36]. Studies, have shown that quinoa can tolerate moderate (150 mM NaCl) to high levels (750 mM NaCl) of salinity [15].…”
Section: Tolerance Of Quinoa Cultivars To the Salt And Alkali Stressmentioning
confidence: 99%
“…The tolerance and the adaptability of a plant to stress conditions such as salinity or alkalinity are tested by the production of different organic compounds such as proline [35,36]. Studies, have shown that quinoa can tolerate moderate (150 mM NaCl) to high levels (750 mM NaCl) of salinity [15].…”
Section: Tolerance Of Quinoa Cultivars To the Salt And Alkali Stressmentioning
confidence: 99%
“…For example, their response to salinity in Genesis 836 was very different from that in Yubileiny. This may reflect the very different backgrounds of the chickpea accessions, resulting in genotype-specific responses, but may also reflect the multi-faceted response of plants to salt, which involves many other genes [61].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, phosphorylation of the SOS3 and SOS2 complexes leads to the activation of SOS1. As mentioned in Figure 8, the newly activated pathway of SOS3-SOS2 stimulates the transcription of SOS1 and stabilizes the cellular levels of SOS1 mRNA [130][131][132].…”
Section: Salinity Stressmentioning
confidence: 93%
“…In rice, miR319, miR535, miR396b, and ONAC095 were reported to increase cold stress tolerance [47][48][49]147]. Additionally, PIF4 is a key facilitator for auxin biosynthesis and is also required for hypocotyl elongation and high temperature stress tolerance [131]. Xing and Zhang (2010) demonstrated that rice grain yield can be controlled by many quantitative trait loci (QTL) [178] and reported that independent or multiplex editing of these QTL can result in an improved yield [76].…”
Section: Recent Progresses In Genome Editing For Crop Improvementmentioning
confidence: 99%